Naturalism : a critical analysis - Craig, William Lane; Moreland, J. P. (James Porter), 1948- (Routledge studies in twentieth century philosophy., 2002)
Naturalism provides a rigorous analysis and critique of the major varieties of contemporary philosophical naturalism. The authors advocate the thesis that contemporary naturalism should be abandoned, in light of the serious objections raised against it. Contributors draw on a wide range of topics including: epistemology, the philosophy of science, the philosophy of mind and agency, and natural theology.